The WArP Experiment: A Double-Phase Argon Detector for Dark Matter Searches. (30th April 2014) - Zani, Andrea
Abstract : Cryogenic noble liquids emerged in the previous decade as one of the best media to perform WIMP dark matter searches, in particular due to the possibility to scale detector volumes to multiton sizes. The WArP experiment was then developed as one of the first to implement the idea of coupling Argon in liquid and gas phase, in order to discriminate β / γ -interactions from nuclear recoils and then achieve reliable background rejection. Since its construction, other projects spawned, employing Argon and Xenon and following its steps. The WArP 100l detector was assembled in 2008 at the Gran Sasso National Laboratories (LNGS), as the final step of a years-long R&D programme, aimed at characterising the technology of Argon in double phase for dark matter detection. Though it never actually performed a physics run, a technical run was taken in 2011, to characterise the detector response.